Tight junction protein changes in irritable bowel syndrome: the relation of age and disease severity - Sang Un Kim; Ji A Choi; Man-Hoon Han; Jin Young Choi; Ji Hye Park; Moon Sik Kim; Yong Hwan Kwon (The Korean Journal of Internal Medicine)
Background/Aims The etiology of irritable bowel syndrome (IBS) is associated with intestinal mucosal barrier damage. However, changes in the tight junction (TJ) proteins in IBS have not been fully elucidated. This study aimed to evaluate TJ protein changes in IBS patients and the relationship between aging and disease severity. Methods Thirty-six patients with IBS fulfilling the Rome IV criteria and twenty-four controls were included. To evaluate the change of TJ in the colonic mucosa, quantitative reverse transcription polymerase chain reaction, western blot, and immunohistochemistry (IHC) were performed, respectively. Results The entire IBS group (n = 36) exhibited decreased levels of claudin-1 and -2 mRNA compared to the control group (n = 24), with statistical significance (p < 0.05). Additionally, in western blot analyses, both claudin-1 and ZO-1 levels were significantly reduced in the IBS group compared to the control group (n = 24) (p < 0.05). IHC analysis further revealed that ZO-1 expression was significantly lower in the IBS group than in the control group (p < 0.001). This trend of reduced ZO-1 expression was also observed in the moderate-to-severe IBS subgroup (p < 0.001). Significantly, ZO-1 expression was notably lower in both the young- (p = 0.036) and old-aged (p = 0.039) IBS groups compared to their respective age-matched control groups. Subtype analysis indicated a more pronounced decrease in ZO-1 expression with advancing age. Conclusions ZO-1 expression was especially decreased in the aged IBS group. These results suggest that ZO-1 might be the prominent TJ protein causing IBS in the aging population.